Allergy-related stomatitis: a rare case in dental practice - Arinawati, Dian Yosi; Femilian, Afryla (Odonto : Dental Journal, 2023)
Background: Oral mucosa is the first gate of food and water to enter the body. This area, including the lips, is more frequent in contact with various food substances containing flavoring agents; therefore, it is very susceptible to allergy-related stomatitis. This study aims to report the case of allergy-related stomatitis due to food intake.Case: We present a case report of 31 year-old-woman complaining of an uncomfortable and burning sensation in the tongue, hard palate, and lips. The clinical examination showed an erythematous lesion along the mucosal lip. The history revealed that the patient had an atopic allergy to seafood and cold air. She reported that three days before she visited the dentist, she ate seafood with very spicy seasoning. According to the complete blood test, it was revealed that eosinophil and total IgE were high. We diagnose allergy-related stomatitis based on the history, clinical features, and blood test examination. The patient was advised not to eat seafood or spicy food and eliminate the precipitating factors Conclusion: Diagnosis of allergy-related stomatitis can be obtained by anamnesis, clinical examination, and other laboratory testing.